Altered flexor carpi radialis motor axon excitability properties after cerebrovascular stroke - Klein, C.S.; Liu, H.; Zhao, C.; Huang, W. (Frontiers in Neurology, 2023)
Background Spinal motoneurons may become hyperexcitable after a stroke. Knowledge about motoneuron hyperexcitability remains clinically important as it may contribute to a number of phenomena including spasticity, flexion synergies, and abnormal limb postures. Hyperexcitability seems to occur more often in muscles that flex the wrist and fingers (forearm flexors) compared to other upper limb muscles. The cause of hyperexcitability remains uncertain but may involve plastic changes in motoneurons and their axons. Aim To characterize intrinsic membrane properties of flexor carpi radialis (FCR) motor axons after stroke using nerve excitability testing. Methods Nerve excitability testing using threshold tracking techniques was applied to characterize FCR motor axon properties in persons who suffered a first-time unilateral cortical/subcortical stroke 23 to 308 days earlier. The median nerve was stimulated at the elbow bilaterally in 16 male stroke subjects (51.4 ± 2.9 y) with compound muscle action potentials recorded from the FCR. Nineteen age-matched males (52.7 ± 2.4 y) were also tested to serve as controls. Results Axon parameters after stroke were consistent with bilateral hyperpolarization of the resting potential. Nonparetic and paretic side axons were modeled by a 2.6-fold increase in pump currents (IPumpNI) together with an increase (38%–33%) in internodal leak conductance (GLkI) and a decrease (23%–29%) in internodal H conductance (Ih) relative to control axons. A decrease (14%) in Na+ channel inactivation rate (Aah) was also needed to fit the paretic axon recovery cycle. “Fanning out” of threshold electrotonus and the resting I/V slope (stroke limbs combined) correlated with blood potassium [K+] (R = −0.61 to 0.62, p< 0.01) and disability (R = −0.58 to 0.55, p < 0.05), but not with spasticity, grip strength, or maximal FCR activity. Conclusion In contrast to our expectations, FCR axons were not hyperexcitable after stroke. Rather, FCR axons were found to be hyperpolarized bilaterally post stroke, and this was associated with disability and [K+]. Reduced FCR axon excitability may represent a kind of bilateral trans-synaptic homeostatic mechanism that acts to minimize motoneuron hyperexcitability.